SOCIAL DEVELOPMENT OF GENDER MARKER AND MANDARIN CHINESE AFFIXOID - Depner, Shelley Ching (PEOPLE: International Journal of Social Sciences, 2020)
This study focuses on the recent morphological development -jie ‘sister’ in Mandarin Chinese. For example, in zhùpǎo-jiě 助跑姐 ‘a woman who ran up to pretend something’ -jie is an affixoid. Our data are taken from Taiwan News Smart Web (2019) and are examined within a semantic and morphological framework. The goal of the study is to investigate the semantic and morphological attributes of [X + jie] nominals and to find out social development the nominals revealed. The findings show that, semantically, [X + jie] refers to the outer appearance, emotion, and behavior of the targeted female. Morphologically, the nominals could be in sentential form and undergo omission, reversion, modification, etc. before reaching suffixation formatting with the affixoid. The high productivity of the gender marker -jie brings the social development of this Chinese speaking society to light. [X + jie] nominals demonstrate social activity, cultural organization, political event, and language contact in Taiwan.